IJTIHAD POLITIK NAHDLATUL ULAMA DALAM KONFIGURASI PEMIKIRAN FIKIH SIYASAH KH MA. SAHAL MAHFUDH - Solikhudin, Muhammad (IAIN Tulungagung, 2021)
The article presented by this author describes the political ijtihad of Nahdlatul Ulama (NU) which is associated with the political thought of KH MA. As is well known, NU is an organization that has an important contribution to building the nation-state and the basic framework of a democratic Indonesian political system. NU and Kiai Sahal have a distinctive political style because they can bring up dialectical reasoning between ahl al-sunnah wa al-jama'ah (Aswaja) and local traditions that lead to the indigenization of Islamic political thought that forms NU's distinctive knowledge. According to the author's understanding, NU's political ijtihad is realistic, inclusive and emphasizes free and honest dialogue between ideologies, cultures and philosophical thoughts to find a system of structuring society that prioritizes the realization of the goals of human life. To realize the purpose of life, there must be a legitimate and authoritative power to carry out its duties and functions. According to NU, the need for legitimate and authoritative power is both theological and sociological. The configuration of Kiai Sahal's political reasoning lies in three things. First, national politics as high-level politics. Second, Islam is an inspiration, not a political aspiration. Third, siyasah fikih is developed in the corridor of national welfare. In this context, siyasah fikih is used as an analytical tool to build a civil society based on three important aspects, including that government is not a right that is prioritized only for certain groups, a government that is not repressive and dictatorial as well as the participation of the community in the administration of government.